A technical guideline on integrated aquaculture performance assessment - Zeller, Manfred; Khor, Ling; Tran, Nhuong; Shikuku, Kelvin; Rajaratnam, Surendran; Chan, Chin Yee; Aung, Yee; Campos, Natalia (WorldFish, 2022)
The aim of this guideline is to provide a methodological approach for an integrated aquaculture performance assessment. It was developed as a deliverable of the Scaling Systems and Partnerships for Accelerating the Adoption of Improved Tilapia Strains by Small-Scale Fish Farmers (SPAITS) project. One of the main outputs of the project is to conduct an integrated performance assessment of improved tilapia strains in participating small-scale fish farming households in Myanmar. The integrated assessment comprises three domains: economic, social and environmental. We use the experience from SPAITS for illustration. The development of this technical guideline also draws on lessons from other projects. More specifically, the guideline focuses on assessing the performance of aquaculture technologies, such as improved fish strains, but it can also be used to assess innovations, such as business models. Section 2 of this report shows the steps to implement and operationalize the assessment together with tools and approaches for data collection. Section 3 illustrates the conceptual framework for a statistical performance assessment and non-statistical/qualitative assessment, focusing on gender scoping. The details of how to analyze the quantitative and qualitative data collected are explained in Section 4.